Nilai Pendidikan Karakter dalam Peribahasa Ternate (Sarana Pembelajaran pada Anak) - Nurbaya Nurbaya (Peneliti.net, 2023)
Proverbs are a form of literary work. Proverb has a positive value in the life of a society, especially in the people of Ternate. One of the values in the literary work serves as a means of character education for a child. This study aims to explain the values of character education in Ternate proverbs. The research method uses a qualitative descriptive approach. Research data were collected through observation, interviews and literature study from Ternate reference books containing Ternate proverbs. While data analysis is done by identifying and classifying proverbs based on the educational values contained therein. The research findings show that the values of character education in Ternate proverbs are: religious, polite in language and behavior, patience, responsibility, love of knowledge, hard work, caution or alertness, maintaining trust, mutual affection, mutual respect, mutual assistance and Social care. These values can be implemented in daily practice in the family, community and school environment in forming good children's character